Psychological study of personal readiness for change and actual functional states of adolescents (Хабаршы. Психология және социология сериясы, 2025)
This study is aimed at studying the psychological aspects of adolescents' personal readiness for change and their functional conditions. Modern teenagers face a lot of social and psychological changes, so their ability to adapt plays an important role. The main purpose of the study is to study the features of the current functional state and psychological readiness of adolescents for changes.The scientific and practical significance of the study lies in the fact that its results can be used to develop programs aimed at providing effective assistance to adolescents during psychological support and counseling. The results are especially relevant for improving methods of psychocorrection and stress management.In the course of the study, the methods "Fatigue – Monotony – Boredom – Stress" and "Personal change readiness survey" were used, assessing the functional conditions of adolescents and their readiness for change. The results showed a high level of mental fatigue and stress in adolescents, which has a negative impact on their adaptation. Despite the fact that most teenagers have a low level of qualities such as passion, resourcefulness, courage and adaptability, their optimism is at a very high level, and self-confidence and tolerance to uncertainty are manifested at an average level, which indicates the need for additional support and motivation for their development.The results of the study can also serve as a basis for practical recommendations to school psychologists and teachers on the development of emotional and psychological stability of students.This study contributes to the understanding of the main factors affecting the personal development of adolescents and their psychological stability, and also contributes to improving the effectiveness of psychological support programs in the educational process.Keywords: personal readiness, functional conditions, stress, fatigue, psychological stability.